2018
DOI: 10.1002/maco.201709894
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical corrosion behavior of Ti‐10V‐2Fe‐3Al in different corrosive media

Abstract: The electrochemical corrosion behavior of Ti‐10V‐2Fe‐3Al in different corrosive media namely, artificial sea water solution, Hank's solution, 0.5 M sulfuric acid, and 0.5 M hydrochloric acid solution has been investigated. Corrosion rates are evaluated using open circuit potential, current time transient, Tafel extrapolation potentiodynamic polarization curves, and electrochemical impedance spectroscopy. The results show that this alloy has lower corrosion rate in alkaline solution due to formation of thick, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
(63 reference statements)
2
8
0
Order By: Relevance
“…[22,23] In particular, vanadates in NaCl solution can act as modest anodic as well as cathodic inhibitors under specific conditions. [22][23][24] A. S. Bhushan et al [25] studied the anticorrosion behavior of Ti-10 V-2Fe-3Al alloy in different corrosive media such as: artificial sea water, Hank's solution, 0.5 M H 2 SO 4 , and 0.5 M HCl. They evoked an important anticorrosion rate in alkaline solution thanks to the formation of thick, compact, and stable passive film.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22,23] In particular, vanadates in NaCl solution can act as modest anodic as well as cathodic inhibitors under specific conditions. [22][23][24] A. S. Bhushan et al [25] studied the anticorrosion behavior of Ti-10 V-2Fe-3Al alloy in different corrosive media such as: artificial sea water, Hank's solution, 0.5 M H 2 SO 4 , and 0.5 M HCl. They evoked an important anticorrosion rate in alkaline solution thanks to the formation of thick, compact, and stable passive film.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, vanadates in NaCl solution can act as modest anodic as well as cathodic inhibitors under specific conditions [22–24] . A. S. Bhushan et al [25] . studied the anticorrosion behavior of Ti‐10 V‐2Fe‐3Al alloy in different corrosive media such as: artificial sea water, Hank's solution, 0.5 M H 2 SO 4 , and 0.5 M HCl.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that all specimens have reached a sufficient steady state with a stability lower than 1 mV/s. All curves displayed an increase of potential in the positive direction starting from the beginning of the test until a steady state was reached, and they showed no sign of noteworthy oscillation, which is an indication of passive film growth and stabilization . As seen in the figure, the activity of 316 stainless steel and CoCrMo alloy were considerably higher (>0.3 V) than the other materials.…”
Section: Resultsmentioning
confidence: 84%
“…Besides, the corrosion potential (E corr ) was becoming more electrochemically negative. E corr values showed that when the value becomes more negative, the Tafel curve is prone to the less noble region, and the corrosion rate is increasing [22][23][24]. The calculated corrosion rate in the highest molarity 1.00 M H 2 SO 4 is 4.75 x 10 6 mpy.…”
Section: Tabmentioning
confidence: 99%